Azaisoindigo conjugated polymers for high performance n-type and ambipolar thin film transistor applications. Issue 41 (4th October 2016) - Yue, Wan; Nikolka, Mark; Xiao, Mingfei; Sadhanala, Aditya; Nielsen, Christian B.; White, Andrew J. P.; Chen, Hung-Yang; Onwubiko, Ada; Sirringhaus, Henning; McCulloch, Iain
Abstract : Two azaisoindigo copolymers have been reported for high performance n-type and ambipolar thin film transistor application. Abstract : Two new alternating copolymers, PAIIDBT andPAIIDSe have been prepared by incorporating a highly electron deficient azaisoindigo core. The molecular structure and packing of the monomer is determined from the single crystal X-ray diffraction. Both polymers exhibit high EAs and highly planar polymer backbones. When polymers are used as the semiconducting channel for solution-processed thin film transistor application, good properties are observed. A–A typePAIIDBT exhibits unipolar electron mobility as high as 1.0 cm 2 V −1 s −1, D–A typePAIIDSe exhibits ambipolar charge transport behavior with predominately electron mobility up to 0.5 cm 2 V −1 s −1 and hole mobility to 0.2 cm 2 V −1 s −1 . The robustness of the extracted mobility values are also commented on in detail. Molecular orientation, thin film morphology and energetic disorder of both polymers are systematically investigated.